Impact of Social Media on Mental Health among Medical Students of Private Medical College, Sargodha (Medical Forum Monthly, 2021)
Objective: To evaluate the degree of impact and relationship between the use of the social media on student’s mental health.Study Design: Descriptive cross sectional studyPlace and Duration of Study: This study was conducted at the Medical Students of Rai Medical Collage, Sargodha Pakistan from 10 March 2020 to 10 May 2020.Materials and Methods: The sample of the study was selected through non-probability volunteer sampling techniques. It was consisting of 150 WhatsApp users comprising of 41 male and 109 female students. Data were collected through a self-developed questionnaire WhatsApp use patterns questionnaire (WUPQ) for measuring the uses of social media networks. To measure the depression and anxiety level of the respondents Hospital Anxiety and Depression Scale (HADS) was used.Results: Results shows social media usage has positive and significant correlation with mental health.Conclusion: A proper formatted assessment for these psychological abnormalities must be part and parcel of all such programs with special focus on underline causative role of non-judicious use of social media.